2004
DOI: 10.1002/jsfa.1628
|View full text |Cite
|
Sign up to set email alerts
|

Antinutritional and/or toxic factors in soybean (Glycine max (L) Merril) seeds: comparison of different cultivars adapted to the southern region of Brazil

Abstract: Soybean (Glycine max (L) Merril) seeds are known to contain different proteins displaying antinutritional and/or toxic effects, such as soybean agglutinin (an N-acetylgalactosamine-specific lectin), proteinase inhibitors (Kunitz-and Bowman-Birk-type trypsin and chymotrypsin inhibitors) and urease (seed and tissue isoforms). Two other toxic proteins were previously isolated from soybeans, soyatoxin (21 kDa) and soybean toxin (18.4 kDa), which are immunologically related to canatoxin, a toxic protein from Canava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 48 publications
(67 reference statements)
1
19
0
Order By: Relevance
“…For to pigs deprecreased ADG by 78% for CSB, 60% for LF, and 35% for LFKF compared with the ADG achieved by pigs fed the same variety but extruded. This results and others (Brune et al, 2010;Becker-Ritt et al, 2004;Vasconcelos et al, 1997) prove that variability in the amounts of these components (proteases inhibitors and lectins) can be affect by cultivars differences. As observed, there seems great potential for reduction in content of anti-nutrients within GM soybeans, as studies have shown that the isogenic variant lacking the Kunitz trypsin inhibitor and other soybean variants low in Kunitz trypsin inhibitor are nutritionally superior to conventional raw soybeans but not as good as commercial soybean meal.…”
Section: Storage and Genetic Varietysupporting
confidence: 74%
“…For to pigs deprecreased ADG by 78% for CSB, 60% for LF, and 35% for LFKF compared with the ADG achieved by pigs fed the same variety but extruded. This results and others (Brune et al, 2010;Becker-Ritt et al, 2004;Vasconcelos et al, 1997) prove that variability in the amounts of these components (proteases inhibitors and lectins) can be affect by cultivars differences. As observed, there seems great potential for reduction in content of anti-nutrients within GM soybeans, as studies have shown that the isogenic variant lacking the Kunitz trypsin inhibitor and other soybean variants low in Kunitz trypsin inhibitor are nutritionally superior to conventional raw soybeans but not as good as commercial soybean meal.…”
Section: Storage and Genetic Varietysupporting
confidence: 74%
“…In its toxicological assessment of the increase in lectin activity, the GMO Panel took into account the following: The toxicity of raw soybean lectins is low compared to other commonly consumed legumes (Nasi et al., ), consisting of reduced growth performance and transient small intestine hypertrophy in experimental feeding studies (Grant et al., ). Current industrial and traditional home processing practices are known to considerably reduce lectin content and/or activity in legumes, including soybean (Liener, ; Duranti and Gius, ; OECD ), and the safe use of soybean depends on such practices (König et al., ). However, it cannot be excluded that residual lectin activity is still present in processed soybean products (Peumans and Van Damme, ; Rizzi et al., ; Vasconcelos and Oliveira, ). The observed increase was considered in the context of the high variability reported for lectin activity and lectin protein content in raw soybean (Becker‐Ritt et al., ; OECD, ; Maria John et al., ). Regarding any possible impact of the observed increase on the levels of residual activity in processed products, it can be considered that (measurable) residual activity is also characterised by high variability, as observed across different products (Calderon de la Barca et al., ) and between different samples of the same product (Maenz et al., ). …”
Section: Assessmentmentioning
confidence: 99%
“…One compound used in the plant defense systems is a trypsin inhibitor, which reduces the activity of trypsin and other proteases. Therefore, it reduces the amino acid bioavailability in many organisms, including humans (Becker-Ritt et al 2004). This kind of inhibitors are mainly found in the seeds and grains of leguminous plants and besides their importance to human nutrition, they modulate process into and out of the cell, interfere with the storage of nitrogen and act as defense compounds against herbivorous, pests, parasites and pathogens (Vasconcelos et al 1994;Carlini and Grossi-de-As 2002;Follmer and Carlini 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Soybeans contain several inhibitors, but the Kunitz inhibitor (STI) is considered to be the primary one. All of them inhibit the chymotrypsin to a lesser extent compared to trypsin and the Kunitz inhibitor has been shown to be the best pancreatic inhibitor (Carlini and Grosso-de-As 2002;Becker-Ritt et al 2004). Soybean (Glycine max (L) Merril) seeds are known to contain different proteins displaying nutritional, antinutritional and/or toxic effects, such as soybean agglutinin (as Nacetylgalactosamine-specific lectin), proteinase inhibitors (Kunitz and Bowman-Birk type's trypsin and chymotrypsin inhibitors) and urease (seed and tissue isoforms).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation